Features of Activity of the Phenylpropanoid Biosynthesis Pathway in Melanin-Accumulating Barley Grains - Glagoleva, Anastasiia Y.; Vikhorev, Alexander V.; Shmakov, Nikolay A.; Morozov, Sergey V.; Chernyak, Elena I.; Vasiliev, Gennady V.; Shatskaya, Natalia V.; Khlestkina, Elena K.; Shoeva, Olesya Y. (Frontiers in Plant Science, 2022)
Barley (Hordeum vulgare L.) grain pigmentation is caused by two types of phenolic compounds: anthocyanins (which are flavonoids) give a blue or purple color, and melanins (which are products of enzymatic oxidation and polymerization of phenolic compounds) give a black or brown color. Genes Ant1 and Ant2 determine the synthesis of purple anthocyanins in the grain pericarp, whereas melanins are formed under the control of the Blp1 gene in hulls and pericarp tissues. Unlike anthocyanin synthesis, melanin synthesis is poorly understood. The objective of the current work was to reveal features of the phenylpropanoid biosynthesis pathway functioning in melanin-accumulating barley grains. For this purpose, comparative transcriptomic and metabolomic analyses of three barley near-isogenic lines accumulating anthocyanins, melanins, or both in the grain, were performed. A comparative analysis of mRNA libraries constructed for three stages of spike development (booting, late milk, and early dough) showed transcriptional activation of genes encoding enzymes of the general phenylpropanoid pathway in all the lines regardless of pigmentation; however, as the spike matured, unique transcriptomic patterns associated with melanin and anthocyanin synthesis stood out. Secondary activation of transcription of the genes encoding enzymes of the general phenylpropanoid pathway together with genes of monolignol synthesis was revealed in the line accumulating only melanin. This pattern differs from the one observed in the anthocyanin-accumulating lines, where — together with the genes of general phenylpropanoid and monolignol synthesis pathways — flavonoid biosynthesis genes were found to be upregulated, with earlier activation of these genes in the line accumulating both types of pigments. These transcriptomic shifts may underlie the observed differences in concentrations of phenylpropanoid metabolites analyzed in the grain at a late developmental stage by high-performance liquid chromatography. Both melanin-accumulating lines showed an increased total level of benzoic acids. By contrast, anthocyanin-accumulating lines showed higher concentrations of flavonoids and p-coumaric and ferulic acids. A possible negative effect of melanogenesis on the total flavonoid content and a positive influence on the anthocyanin content were noted in the line accumulating both types of pigments. As a conclusion, redirection of metabolic fluxes in the phenylpropanoid biosynthesis pathway occurs when melanin is synthesized.